The mushroom matrix: an engineered mycelium-derived biochar platform for advanced biotechnological applications - Tian, Xingguo; Du, Tian-Ye; Lu, Wenhua; Kumla, Jaturong; Tarafder, Entaj; Priyadarshani, Tikka Dewage Chamarika; Perera, Rekhani Hansika; Hapuarachchi, Kalani Kanchana; Suwannarach, Nakarin (Frontiers in Bioengineering and Biotechnology, 2025)
Mushroom cultivation generates vast amounts of spent substrate, while the controlled growth of fungal mycelium offers a dedicated feedstock for advanced materials. This review synthesizes the science of mushroom-derived biochars, a distinct class of biomaterials sourced from this underutilized biomass. This review demonstrates that the inherent biological architecture of fungal matter, specifically its chitinous framework and nitrogen-rich composition, is preserved through pyrolysis to create biochars with superior functionality. We demonstrate how these materials transcend their traditional role as soil amendments to serve as programmable platforms for biotechnology. The review explores how pyrolysis parameters and advanced synthesis methods, such as chemical activation and co-pyrolysis, can be precisely tuned to engineer bespoke properties, including ultra-high surface areas (>1200 m2/g) and enhanced contaminant affinity. A central focus is placed on the unique capacity of mushroom biochars to act as prebiotic scaffolds that directly modulate microbial communities, drive biogeochemical cycles, and facilitate breakthrough applications. By mapping the journey from mycelium to advanced mycomaterials, this work charts a course for the intentional design of tailored myco-materials to address pressing global challenges in environmental remediation, sustainable agriculture, energy storage, and sensing technologies.